2016
DOI: 10.4067/s0717-75182016000300002
|View full text |Cite
|
Sign up to set email alerts
|

Efecto De Una Dieta Personalizada en Mujeres Embarazadas Con Sobrepeso U Obesidad

Abstract: Efecto de una dieta personalizada en mujeres embarazadas con sobrepeso u obesidadPersonalized diet effect in pregnant obese or overweight women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Una alimentación equilibrada, es una necesidad, un reto y algunas veces una dificultad para muchos seres humanos, al solventar dicha necesidad es donde se realizan actividades que se convierten en hábitos y prácticas saludables y no saludables para la vida (14) . Las adolescentes con hipertensión inducida por la gestación, no son la excepción, la cultura donde se desenvuelven es diversa.…”
Section: Discussionunclassified
“…Una alimentación equilibrada, es una necesidad, un reto y algunas veces una dificultad para muchos seres humanos, al solventar dicha necesidad es donde se realizan actividades que se convierten en hábitos y prácticas saludables y no saludables para la vida (14) . Las adolescentes con hipertensión inducida por la gestación, no son la excepción, la cultura donde se desenvuelven es diversa.…”
Section: Discussionunclassified
“…A study in Mexico determined if the nutritional status of overweight and obese pregnant women improved by implementing a personalized diet. These results indicated that the group of sugars had a greater decrease in consumption (15.1%) than the other food groups evaluated [ 5 ]. This could be attributed to the fact that the personalized diet emphasized eating foods with low glycemic index.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important contributors to GWG are eating habits. Elevated sugars consumption of foods with high energy value and high added sugars predisposes these women to excessive GWG [ 5 , 6 ]. The study by Renault et al [ 6 ] revealed that large GWG is more related to intake of added sugars than to saturated fats.…”
Section: Introductionmentioning
confidence: 99%